Fluid shear stress-mediated mechanotransduction in circulating leukocytes and its defect in microvascular dysfunction. (7th May 2021) - Shin, Hainsworth Y.; Fukuda, Shunichi; Schmid-Schönbein, Geert W.
Abstract: Leukocytes (neutrophils, monocytes) in the active circulation exhibit multiple phenotypic indicators for a low level of cellular activity, like lack of pseudopods and minimal amounts of activated, cell-adhesive integrins on their surfaces. In contrast, before these cells enter the circulation in the bone marrow or when they recross the endothelium into extravascular tissues of peripheral organs they are fully activated. We review here a multifaceted mechanism mediated by fluid shear stress that can serve to deactivate leukocytes in the circulation. The fluid shear stress controls pseudopod formation via the FPR receptor, the same receptor responsible for pseudopod projection by localized actin polymerization. The bioactivity of macromolecular factors in the blood plasma that interfere with receptor stimulation by fluid flow, such as proteolytic cleavage in the extracellular domain of the receptor or the membrane actions of cholesterol, leads to a defective ability to respond to fluid shear stress by actin depolymerization. The cell reaction to fluid shear involves CD18 integrins, nitric oxide, cGMP and Rho GTPases, is attenuated in the presence of inflammatory mediators and modified by glucocorticoids. The mechanism is abolished in disease models (genetic hypertension and hypercholesterolemia) leading to an increased number of activated leukocytes in the circulation with enhanced microvascular resistance and cell entrapment. In addition to their role in binding to biochemical agonists/antagonists, membrane receptors appear to play a second role: to monitor local fluid shear stress levels. The fluid shear stress control of many circulating cell types such as lymphocytes, stem cells, tumor cells remains to be elucidated.